Investigation of Equipment Elements of the Niğde Ömer Halisdemir University Campus in Terms of Aesthetics and Functional Properties - Orhun Soydan (Turkish Journal of Agriculture: Food Science and Technology)
In this study, equipment elements which have been used in Niğde Ömer Halisdemir University campus, were analysed considering various criteria in terms of landscape architecture. In this study, lighting and flooring elements, trash cans, sitting elements etc. were evaluated considering some criteria such as maintenance, design, ergonomics, etc. Within the scope of the study, it has been determined whether the equipment elements in the campus meet the people needs. There are insufficient number of seating elements in the campus, security problems occur due to the lack of lighting elements in certain places. The bus stops in the campus are sufficient numerically, and they are in suitable areas in terms of location. In addition, the number of telephone booths and the number of trash cans in the campus are insufficient. The designs of the equipment elements are similar, and equipment elements have traditional design. As paving elements, key paving stones are used on pedestrian roads, so that in some areas, collapses occur, so fall, snag, etc. on pedestrian roads. Finally, suggestions for using equipment elements in campus areas were developed.